Restoration of Degraded Lands through Plantation Forests (Global Journal of Science Frontier Research, 2014)
Degradation of soil is a matter of serious concern. Vast area of land all over the world has been converted into unproductive and degraded lands. Eco-restoration through plantation forests is the most effective technique to reclaim the degraded ecosystem. Six dominant species viz, Dalbergia sissoo, Pongamia pinnata, Tectona grandis, Gmelina arborea, Azadirachta indica and Cassia siamea were studied for restoration of degraded ecosystem. No amendment was given during plantations except farm yard manure (FYM), Urea and Aldrin as soil insecticide before planting the seedlings. The density of plants was 3333 ha-1. The present paper deals with the edaphic development of degraded coal mine spoil through establishment of six dominant tree species at Northern Coalfield Limited, Singrauli. The results indicated that the bulk density of the reclaimed sites was gradually reduced with the age of the plantations. The soil organic carbon, pH, EC, water holding capacity and nutritional status were found increasing with the age of the plantations. As regards the organic carbon in mine spoil under different tree cover, it was found improved to the maximum extent during 16 years interval in Dalbergia sissoo (358%) followed by Azadirachta indica (317.8%), Pongamia pinnata (273.8%), Tectona grandis (233.3%) and others. The similar increasing trend was found in pH.
Keywords: restoration; plantation forests; degraded lands; productive ecosystem; dominant tree species